2023
DOI: 10.1186/s12870-023-04368-8
|View full text |Cite
|
Sign up to set email alerts
|

Independent flavonoid and anthocyanin biosynthesis in the flesh of a red-fleshed table grape revealed by metabolome and transcriptome co-analysis

Abstract: Background Red flesh is a desired fruit trait, but the regulation of red flesh formation in grape is not well understood. ‘Mio Red’ is a seedless table grape variety with light-red flesh and blue-purple skin. The skin color develops at veraison whereas the flesh color develops at a later stage of berry development. The flesh and skin flavonoid metabolomes and transcriptomes were analyzed. Results A total of 161 flavonoids were identified, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…15 Mechanism of Color Change: The uniqueness of this tea is mainly due to its distinctive purple color, which occurs as a result of hyper-accumulation of anthocyanin in the plant. Anthocyanins are biosynthesized from the flavonoid biosynthetic pathway in the cytosol of the cell, and then the glycosylated end products are deposited in the vacuole 16 . Plant anthocyanins show different transition in colors like red, purple, or reddish violet, in the form of cyanine glycosides after methylation, acetylation and glycosylation from an anthocyanin monomer.…”
Section: Morphological Observation Through Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Mechanism of Color Change: The uniqueness of this tea is mainly due to its distinctive purple color, which occurs as a result of hyper-accumulation of anthocyanin in the plant. Anthocyanins are biosynthesized from the flavonoid biosynthetic pathway in the cytosol of the cell, and then the glycosylated end products are deposited in the vacuole 16 . Plant anthocyanins show different transition in colors like red, purple, or reddish violet, in the form of cyanine glycosides after methylation, acetylation and glycosylation from an anthocyanin monomer.…”
Section: Morphological Observation Through Standardmentioning
confidence: 99%
“…17 Studies have revealed that activation of the R2R3-MYB transcription factor (TF), anthocyanin1 (CsAN1) specifically upregulated the bHLH TF CsGL3 and anthocyanin late biosynthetic genes (LBGs) to accumulate in purple tea. It was also found that CsAN1 interacts with bHLH TFs (CsGL3 and CsEGL3) and WD-repeat protein CsTTG1 to form the MYB-bHLH-WDR (MBW) complex 16 . In leaves of purple tea, this MYB-bHLH-WDR complex regulates anthocyanin accumulation by activating mRNA expression of F3H, DFR and ANS.…”
Section: Fig 1: Mechanism Of Color Changementioning
confidence: 99%
“…These values, however, depended on the cultivar and maturity stage. The major anthocyanins found in the mangosteen pericarp were cyanidin‐3‐sophoroside and cyanidin‐3‐glucoside (Jamil et al., 2023; Palapol, Ketsa, Stevenson, et al., 2009), while the main anthocyanin(s) identified in red apple was cyanidin‐3‐ O ‐galactoside (Y. Liu et al., 2013; Shi et al., 2022), in Malay apple was cyanidin‐3‐ O ‐glucoside (Kotepong et al., 2019), in blueberry was malvidin‐3‐galactoside (S. Wang, Wang, et al., 2022), in sweet cherry was cyanidin‐3‐rutinoside with cyanidin‐3‐glucoside being the second most prominent (Chaovanalikit & Wrostad, 2004), in both plum (Usenik et al., 2009) and litchi was cyanidin‐3‐rutinoside (He et al., 2022; Rivera‐López et al., 1999; Z. Zhang et al., 2004), in red pomegranate were cyanidin‐3,5‐diglucoside and cyanidin‐3‐glucoside (Zhao et al., 2015), in table grape were cyanidin‐3,5‐ O ‐diglucoside and cyanidin‐3‐ O ‐glucoside (Kőrösi et al., 2022; Lu et al., 2023), in muscadine grape was delphinidin‐3,5‐diglucoside (Yuzuak & Xie, 2022), in rambutan was cyanidin‐3‐ O ‐glucoside (Monrroy et al., 2020), in red raspberry was cyanidin‐3‐ O ‐sophoroside (Teng et al., 2017), and in strawberry was pelargonidin‐3‐ O ‐glucoside (Cho et al., 2021; da Silva et al., 2007; Dzhanfezova et al., 2020; Karaaslan & Yaman, 2017; Miao et al., 2016). There were, therefore, considerable differences among these different fruits in the type of glycoside and the type of anthocyanidin that was present.…”
Section: Anthocyanin Biosynthetic Pathwaymentioning
confidence: 99%
“…The genes that have been identified as being involved in the regulation of the anthocyanin biosynthetic pathway in a number of different fruits consist of many genes that encode the enzymes involved in the synthesis of anthocyanins (Table 1). The high expression of genes shown in Table 1 has been correlated with anthocyanin accumulation in both colored and noncolored fruit, and their skin and flesh, in a range of fruits including apple (Honda et al., 2002; C. Ma et al., 2019; Shi et al., 2022), grape (Boss et al., 1996; Ge et al., 2022; Jeong et al., 2004; Lu et al., 2023), litchi (He et al., 2022; Lai et al., 2014), mango (Bajpai et al., 2018), Malay apple (Kotepong et al., 2011, 2019), peach (Cao et al., 2018; X. Liu et al., 2019; Rahim et al., 2014; Tsuda et al., 2004; Ye et al., 2019), pear (J. Liu, Deng, et al., 2021), and pomegranate (Zhao et al., 2015).…”
Section: Genes Regulating Biosynthesis Of Anthocyaninsmentioning
confidence: 99%
“…As consumer demand for fresh products transcends seasonal boundaries, the need to extend the shelf life of table grapes through effective cold storage practices becomes paramount. Moreover, offering the consumer grapes with high nutraceutical properties even many days after harvesting is essential, considering that consuming fresh grapes significantly benefits human health [14][15][16]. The intricate balance between maintaining optimal conditions for grape preservation and the inherent perishability of this fruit poses a fascinating challenge [17].…”
Section: Introductionmentioning
confidence: 99%